2023
DOI: 10.1155/2023/5490068
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Social Beliefs on Consumption of Dairy Products and Its Predicting Factors Based on the Transtheoretical Model: A Population-Based Study

Abstract: Background. Social beliefs on the consumption of dairy products are associated with health conditions, and the aim of this study is to investigate associated factors with the rate of dairy product intake, in accordance with social health-related beliefs and the elements predicting dairy consumption, based on the transtheoretical Model (TTM). Methods. 981 subjects (chosen from Mashhad citizens, Iran) were surveyed in random public places in 2014, using demographic surveys and questionnaires based on TTM and adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…Family education score was negatively related to yogurt, cheese and total dairy consumption. Vakili et al, also showed that People with a high school diploma and lower levels of education consumed substantially more dairy products than more educated ones ( 67 ). Contrary to these findings, some other cross-sectional studies in Iran ( 66 ), indicated that higher education level increases the probability of choosing dairy products.…”
Section: Discussionmentioning
confidence: 99%
“…Family education score was negatively related to yogurt, cheese and total dairy consumption. Vakili et al, also showed that People with a high school diploma and lower levels of education consumed substantially more dairy products than more educated ones ( 67 ). Contrary to these findings, some other cross-sectional studies in Iran ( 66 ), indicated that higher education level increases the probability of choosing dairy products.…”
Section: Discussionmentioning
confidence: 99%
“…Scholars identify time concerns, high prices, and value for money as the most significant value barriers [9]. Demographic and socioeconomic factors, such as price, availability, awareness, and convenience, could affect dietary behavior [10]. Food curiosity and food price inflation were identified as relevant for both willingness to buy and willingness to pay a price premium [11].…”
Section: Introductionmentioning
confidence: 99%